The Taiwan Government Narration of the Russo-Ukrainian War: Domestic and International Implications - Denoisieux,Katherine (2025)
This thesis aimed to analyze how the Taiwanese government narrates the Russo-Ukrainian war and why, regarding their foreign policy efforts and the articulation of a Taiwanese national identity. Twenty-nine articles from the Taiwanese Office of the President published between January and August 2022 were examined. In its discourse, Taiwan drew a parallel with the situation in Ukraine, portraying both as fighting for their freedom and democracy amid authoritarian aggression. This narrative is embedded in a broader story, i.e., the fight for democracy, and calls for unity as a condition for victory. I argue that the goal is to pressure its allies for support in the case of an invasion while deterring the PRC by showing the support the island and Ukraine are receiving. The analysis showed that Taiwan balanced domestic and international constraints by performatively affirming its distinct identity and independence while not pursuing it officially. Democracy and the freedoms attached to it were portrayed as a core national value and justified the Taiwanese positioning on the Ukrainian conflict. As democratization is consensually what distinguishes Taiwan from the PRC, it is the cornerstone of its emerging founding myth, allowing for the creation of an “us” and a “them”.
Keywords: Taiwan; Ukraine; War; National identity; Foreign policy; Geopolitics; Nationalism; Narrative